Action of Antibiotics as Signalling Molecules - V. G. Bulgakova; K. A. Vinogradova; T. I. Orlova; P. A. Kozhevin; A. N. Polin (Антибиотики и Химиотерапия, 2020)
It was thought that antibiotics should be produced by soil microorganisms to inhibit the growth of competitors in natural habitats. Yet it has been shown that antibiotics at subinhibitory concentrations may have a role as signalling molecules providing cell-to-cell communication in bacteria in the environment. Antibiotics modulate gene transcription and regulate gene expression in microbial populations. Subinhibitory concentrations of antibiotics may cause a number of phenotypic and genotypic changes in microorganisms. These transcription changes are dependent on the interaction of antibiotics with macromolecular receptors such as ribosome or RNA-polymerase. Antibiotic signalling and quorum-sensing system are important regulatory mechanisms in bacteria. It was demonstrated that antibiotics interfered with quorum-sensing system.